Investigation of heat transfer performance within annular geometries with swirl-inducing fins using clove-treated graphene nanoplatelet colloidal suspension - Nair S.R.; Oon C.S.; Tan M.K.; Mahalingam S.; Manap A.; Kazi S.N. (Springer Science and Business Media B.V., 2023)
Boundary layers; Fins (heat exchange); Heat transfer performance; Suspensions (fluids); Vortex flow; Annular domain; Annular flows; Annular geometry; CGNP; Colloidal suspensions; Graphene nanoplatelets; Heat transfer performance; Recirculations; Swirl-inducing fin; Vortical structures; Computational fluid dynamics